O Caminho do Professor Doutor Malafaya Baptista - Vida e Obra - Mafalda Inês Ribeirinha de Freitas Gonçalves (2020)
Throughout the History of University of Porto's Faculty of Medicine there are countless examples of Doctors who acquired their knowledge and have excelled as health professionals, professors, researchers and people of culture. Professor Malafaya Baptista (1903-1966) is among these illustrious people who have boosted the growth of Medicine and Science in Portugal. The task of compiling his life and work was made possible thanks to the archives available at "Maximiano Lemos" Museum of Medical History of University of Porto's Faculty of Medicine, as well as information given by his family members. He joined this University simultaneously studying Pharmacy and Medicine, which he concluded in 1926 and 1928. He began his academic career, as a free Assistant in Surgery and Pharmacology. He interned at Faculty of Medicine of Lisbon's Institute of Pharmacology and General Therapeutics and he was a scholar at the Institute for Higher Culture. In 1954, he became Full Professor of Pharmacology and General Therapeutics. He served in relevant positions, including Director of the Clinical Analysis Laboratory at Porto Military Hospital and Pasteur Institute of Lisbon's Director. Was a member of the Portuguese Society of Biology, Medical Sciences of Lisbon and Hydrology. In 1956, he was awarded the second Pfizer Prize from Society of Medical Sciences of Lisbon. He should be remembered for his undeniable contribution to the progress of medical science, particularly in the domain he focused on. This work is more than a historical record - it intends to preserve his work as an example for future generations.